Aperfeiçoamento de modelos numéricos para estimativa de propriedades térmicas do solo - Romio, Leugim Corteze (2019)
Understanding the soil thermal properties, in particular, diffusivity , volumetric capacity and conductivity is important in applications of several related areas, mainly soil-plant-atmosphere interaction. Studies to understand what affects the value of these properties are often related to the closure of the surface energy balance, where these properties are fundamental for determining the heat flux on the surface of the soil. In addition, knowledge of soil thermal properties is critical for soil temperature estimates, an important variable in plant germination and growth studies, as well as engineering studies. In this sense, this work aims to estimate the thermal properties of the soil, using an alternative approach aided by numerical modeling with experimental data collected at two experimental sites in the Pampa biome region over a one year period. The addition of an empirical parameter to the gradient method of solution of Fourier Law of heat conduction was suggested, in order to better represent the observed experimental data. The proposition of the models took into consideration the analysis of the behavior observed in the experimental data. The proposed models were compared with models described in the literature showing better results with the proposed model. In addition, an analysis of daily averages was performed to verify the existence of a relationship between soil thermal properties and soil water content. The results obtained in this thesis indicated that the proposed models better represented the experimental data, compared to models present in the literature. In addition, these results will contribute to surface energy exchange studies, since the proposed methodology improved the estimation of the thermal properties of the soil, consequently the heat flux of the soil, an essential component for surface energy balance closure studies.